Influence of High Temperature Stress on Net Photosynthesis, Dry Matter Partitioning and Rice Grain Yield at Flowering and Grain Filling Stages - Guo-hua LÜ; Yong-feng WU; Wen-bo BAI; Bao MA; Chun-yan WANG; Ji-qing SONG (Journal of Integrative Agriculture, 2013)
Climate change is recognized to increase the frequency and severity of extreme temperature events. At flowering and grain filling stages, risk of high temperature stress (HTS) on rice might increase, and lead to declining grain yields. A regulated cabinet experiment was carried out to investigate effects of high temperature stress on rice growth at flowering and grain-filling stages. Results showed that no obvious decrease pattern in net photosynthesis appeared along with the temperature rising, but the dry matter allocation in leaf, leaf sheath, culm, and panicle all changed. Dry weight of panicle decreased, and ratio of straw to total above ground crop dry weight increased 6–34% from CK, which might have great effects on carbon cycling and green house gas emission. Grain yield decreased significantly across all treatments on average from 15 to 73%. Occurrence of HTS at flowering stage showed more serious influence on grain yield than at grain filling stage. High temperature stress showed negative effects on harvest index. It might be helpful to provide valuable information for crop simulation models to capture the effects of high temperature stress on rice, and evaluate the high temperature risk.